Policy Evaluation Of Performances Allowance using System Dynamics Approach: Case Study Of Indonesia Navy - H. Nugroho, Sukmo; Gunawan, Kazan; .Madhakomala, R. (International Journal of Scientific Research and Management (IJSRM), 2018)
Indonesia Navy (TNI-AL) has implemented a policy in the field of performance management to improve the professionalism of soldiers with the provision of performance allowance. Performance allowances (remuneration) are expected to improve the performance of personnel that will have an effect on improving organizational performance. However, this policy at the level of application still appears some potential problems. Nowadays, the policy has not given a significant influence on the performance, productivity and improvement of the personnel welfare of TNI AL. The provision of performance allowance is not based on achievement, weight and level of work risk on each personnel. The aim of this paper is giving analysis, studies, and research about how the application of remuneration allowance policy of Navy personnel and an impact on performance, soldiers welfare, and public services. This research uses system dynamics (SD) approach to answer a research problem. The result of paper was given analysis that professionalism aspect has weight 7,02; Soldier income aspect has weight 6,73; soldier capability aspect has weight 7,71. The final result showed that public service aspect has weight 4,88; Navy workload aspect has weight 7,18; Job risk aspect has weight 5,12. The final result showed that soldier welfare aspect has weight 6,75; Performance allowance aspect has weight 6,54; social status aspect has weight 6,11